1973
DOI: 10.1007/bf02640489
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride structure of milk fats

Abstract: The enantiomeric nature of the triglycerides of bovine milk fat was reinvestigated by determining the stereospecific distribution of fatty acids in rearranged butterfat, following partial hydrolysis with pancreatic lipase, and in certain molecular distillates of native butterfat, following Grignard degradation. The results with rearranged butterfat confirmed the validity of pancreatic lipase hydrolysis as a means of generating representative diglycerides from milk fat triglycerides. The Grignard degradation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
35
2
2

Year Published

1974
1974
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(41 citation statements)
references
References 53 publications
2
35
2
2
Order By: Relevance
“…On the other hand, the fatty acid combinations and regioisomeric structure of specified ACN/DB (acyl carbon number/number of double bonds) species of TAG can be determined rapidly and with minimal sample preparation, which is not easily achieved by other methods. The results obtained for molecular species analyzed by mass spectrometry (7,8) were in accordance with chromatographic results (1)(2)(3)(4)(5)(6).…”
supporting
confidence: 74%
See 2 more Smart Citations
“…On the other hand, the fatty acid combinations and regioisomeric structure of specified ACN/DB (acyl carbon number/number of double bonds) species of TAG can be determined rapidly and with minimal sample preparation, which is not easily achieved by other methods. The results obtained for molecular species analyzed by mass spectrometry (7,8) were in accordance with chromatographic results (1)(2)(3)(4)(5)(6).…”
supporting
confidence: 74%
“…In addition to fatty acid combinations, the stereospecific positions of fatty acids within each combination affect the biochemical and nutritional properties of TAG. In human milk, 16:0 is predominantly located in sn-2 position of the TAG molecule, whereas 18:0, 18:1, and 18:2 have been reported to be preferentially esterified in sn-1/3 positions (2)(3)(4)(5)(6). Breckenridge et al (3) reported the molar proportion of palmitic acid to be 16, 58, and 6% of total fatty acids in sn-1, sn-2, and sn-3 positions of human milk TAG, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Intact triacylglycerols and diacv8glycerol s-BDMS ethers were resolved according to molecular weight by glc on 3% OV-1 (24). This glc sys-ten1 was also satisfactory for pyrolysis glc of the sn-2,3-diacylgly~erophosghatidylphenols~ Fatty acid methyl esters were analyzed on coIaamns prepared with 18% EGSS-X and 3% SILAR 5CP as previously described (25).…”
Section: Aaa%ysm Oj Lipidsmentioning
confidence: 99%
“…Analyses were accepted only when the results obtained for positions sn-2 and sn-3 calculated by the alternative procedures agreed within 5% (22). No difficulties were caused by the presence of trigiycerides containing short chain fatty acids as reported by others (23), possibly because the . k 9…”
Section: R Esu Ltsmentioning
confidence: 90%